Differences between men and women in response to antiseizure medication use and the likelihood of developing treatment resistant epilepsy. Issue 4 (8th August 2022) - Cepeda, M. Soledad; Teneralli, Rachel E.; Kern, David M.; Novak, Gerald
Abstract: Objective: The prevalence of epilepsy is slightly higher in women than in men and sensitivity to seizure stimuli differs between sexes. Some evidence suggests sex differences in response to antiseizure medications exist mainly due to inconsistent pharmacokinetic differences; however, there is a lack of real‐world evidence examining differences in response to antiseizure medications between men and women. Methods: This was a retrospective population‐based cohort study in five large US healthcare databases. The population included adult patients with epilepsy, newly exposed to levetiracetam, and naive to antiseizure medication. The first exposure to levetiracetam was the index date. The requirement that all patients received the same medication was done to avoid potential confounding due to differences in index treatment. The outcome was the development of treatment resistant epilepsy (TRE), defined as having at least three distinct antiseizure medications in 1 year. The proportion of patients who developed TRE within 1 year following the index date was calculated. To compare the risk of developing TRE between sexes, relative risks (RR) and 95% confidence intervals (CI) were calculated, and estimates were pooled using meta‐analytic techniques stratified by gender and age. Results: A total of 147 334 subjects were included in the databases, 50.8% were women, and 4.27% developed TRE. The comorbid profile differed greatly between men and women; however, the types of epilepsy syndromes observed during baseline were similar between the two groups. Across all databases, women were more likely to develop TRE than men (pooled RR 1.27, 95% CI 1.17‐1.38). Results remained similar when stratified by age. Significance: This study assessed sex differences in response to antiseizure medications using the development of TRE as a proxy for effectiveness. Women newly exposed to levetiracetam were 27% more likely to develop TRE than men, independent of age.